How informative are macroeconomic risk forecasts? An examination of the Bank of England's inflation forecasts - Malte Knüppel; Guido Schultefrankenfeld (Deutsche Bundesbank, 2008)
Macroeconomic risk assessments play an important role in the forecasts of many institutions. However, to the best of our knowledge their performance has not been investigated yet. In this work, we study the Bank of England?s risk forecasts for inflation. We find that these forecasts do not contain the intended information. Rather, they either have no information content, or even an adverse information content. Our results imply that under mean squared error loss, it is better to use the Bank of England?s mode forecasts than the Bank of England?s mean forecasts.
Keywords: C53; C12; E37; 330; Forecast evaluation; risk forecasts; Bank of England inflation forecasts; Inflation; Risiko; Prognose; Bewertung; Informationswert; Großbritannien